1990
DOI: 10.1007/bf02019656
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal ultrasonography in infants and children: Anatomical correlation with fetal preparations

Abstract: Normal sonographic anatomy of the larynx in children was established by studying 40 healthy children and 3 fetuses. The normal anatomy is described on transverse sonograms passing at level of the ventricular bands, the true vocal cords and the subglottis and the interpretation of the sonographic aspect of the larynx is given. Ultrasound of the larynx seems to provide a good analysis of cartilaginous and endolaryngeal structures and can also show the dynamic aspect of the larynx. A pathological case is describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…Transcervical ultrasound generally does not allow a complete evaluation of the adult larynx due to ossification and intraluminal air. On the other hand, the laryngeal cartilages in children are not calcified, so the endolaryngeal structures can be clearly identified in ultrasound images [4,[10][11][12][13]. In our study, we confirmed that ultrasound imaging could clearly show the normal pediatric larynx.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Transcervical ultrasound generally does not allow a complete evaluation of the adult larynx due to ossification and intraluminal air. On the other hand, the laryngeal cartilages in children are not calcified, so the endolaryngeal structures can be clearly identified in ultrasound images [4,[10][11][12][13]. In our study, we confirmed that ultrasound imaging could clearly show the normal pediatric larynx.…”
Section: Discussionsupporting
confidence: 91%
“…Computed tomography (CT) and magnetic resonance imaging (MRI) cannot reveal the mobility of the vocal fold in real time. A preliminary study by Garel et al [4] confirmed that ultrasound (US) imaging could show the normal pediatric larynx. Friedman [5] and Vats et al [6] reported that laryngeal US was useful in diagnosing pediatric VFP.…”
Section: Introductionmentioning
confidence: 80%
“…Paralysis of the vocal cords was excluded by direct observation of their movements during breathing and phonation. 7 Absence of vascular signals on Doppler interrogation associated with the anechoic aspect of the mass in our case excluded the diagnosis of hemangioma. 7 In conclusion, ultrasonographic examination is a noninvasive and easily reproducible way of investigating the infantile larynx and should be performed prior to the endoscopy of the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 51%
“…6 Sonographic examination of the larynx is an easy and useful imaging modality in infants. 2,7,8 It allows a good analysis of the cartilaginous structures, muscles, and endolaryngeal structures. 7,8 As observed in this case, ultrasonography appears to be useful for the differential diagnosis of rare causes of stridor in an ill premature baby.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation